COST-EFFECTIVENESS OF HLA-B*5701 PROSPECTIVE GENETIC SCREENING OF HYPERSENSITIVITY TO ABACAVIR - M B, Kubaeva; J Sh, Gushchina; E E, Loskutova (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: This study was conducted to evaluate the use of genetic tests, before prescribing drugs to reduce not only the level of side effects but also the costs associated with changing therapy. In this paper, the authors analyze the economic efficiency of HLA*5701 prospective screening of hypersensitivity to abacavir (ABC) in the treatment of HIV-infected patients. Methods: A retrospective study was conducted among HIV-infected patients taking first-line antiretroviral therapy and further, based on the results obtained with the ABC-hypersensitivity reactions, analyzed the costs that affect on healthcare system. Results: In the study group of HIV-infected patients, most of the cases belonged to a young, socially active part of the population. Among the study population of patients (n=637), 171 patients were assigned ABC-containing antiretroviral therapy. An increase in costs was found in 67% of cases when ABC-containing first-line therapy was replaced due to the occurrence of undesirable reactions. Conclusion: The results show that, using this screening, we could reduce the costs associated with replacement therapy